SOCIAL RESPONSIBILITY IN SPORT (PEACE BALL PROJECT) - Sebahattin DEVECİOĞLU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
The main purpose of the "Peace Ball Project" is to express that sports has no discrimination of religion, language or race, emphasize that sports is a shared value of mankind and ensure " Peace, Friendship and Brotherhood" by sports. Moreover, within the activities accomplished in the project, an additional campaign will be started to provide sports equipment to male and female children who are interested in sports in the region by creating an awareness about "Children's right to play" and drawing the whole world's attention and interest to kids residing poor districts.UNICEF is making effort for reaching 43 million children in worldwide. Because of many children has the same right to thrive, play, and practice sports.Articles from "Rights of the Child" which went into effect in 2nd of September 1990 and signed by 193 countries; Article 31/1 and 2 In 2015, the United Nations General Assembly adopted the 2030 Agenda for Sustainable Development, which contained a set of 17 Sustainable Development Goals. Paragraph 37 of the Agenda states. Within the framework of The Article 59 of Turkish Republic's Constitution. Understanding, a common goal which was accepted by International Olympic Committee and UN, UNESCO, UNICEF, European Union, Governments, Municipalities, Sports Federations, Universities and Non-Governmental Organizations is; "to achieve more accessible and sustainable sports on neutral and safe grounds, to provide development in underdeveloped regions, to eradicate poverty and inequality, to contribute to education, to convey sport's role in education, health, social, cultural and economics to masses by encouraging lifelong sports and healthy life culture"